Routing metric based on interference measurement for multi-radio multi-channel wireless mesh networks - Wen-jiang JI; Jian-feng MA; Jun-wei ZHANG; Zhuo MA (Tongxin xuebao)
An interference sensing based(ISB)routing metric which mainly depend on the estimation of signal power was introduced for the multi-radio multi-channel wireless mesh networks.The existing metric such like WCETT and iAWARE all have their drawbacks were shown.As shown in the equations of iAWARE,it could be proved that worse background noise corresponds to a better metric value which was imprecise.The iAWARE to make it suited for the environment with background noise was improved,and the isotonic property was regained that the Bellman-Ford and Dijkstra algorithm could be deployed in ISB.The simulation results prove the novel algorithm takes the advantages of higher efficiency both in throughput and end to end delays,compared with the traditional ones HopCount,ETT,WCETT and iAWARE.